2020
DOI: 10.3390/plants9111608
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Integration Increases Sexual Reproductive Performance of the Rhizomatous Grass Hierochloe glabra

Abstract: Clonal plants usually reproduce asexually through vegetative propagation and sexually by producing seeds. Physiological integration, the translocation of essential resources between ramets, usually improves vegetative reproduction. However, how physiological integration affects sexual reproduction has been less studied in clonal grasses. Here, we chose Hierochloe glabra, a major early spring forage of the eastern Eurasian steppe, and conducted a series of field experiments, including sampling reproductive rame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Studies have repeatedly revealed that physiological integration between vegetative ramets and vegetative ramets with the same function via a rhizome or stolon has a positive effect on the survival and growth of the ramets ( Evans and Cain, 1995 ; Dong and Alaten, 1999 ; Song et al., 2013 ; Chen et al., 2015 ), but little research has been performed on the effect of physiological integration between vegetative ramets and reproductive ramets with different functions by tillering node connection on sexual reproductive performance. Our previous studies showed that physiological integration between vegetative and reproductive ramets connected by a tillering node increased sexual reproductive characteristics such as inflorescence biomass, floret number, seed number, seed biomass and the seed-setting rate in H. glabra ( Guo et al., 2020b ) and L. chinensis ( Guo et al., 2020c ). In the present study, by severing connections, we found that physiological integration between vegetative ramets and reproductive ramets connected by a tillering node significantly increased the leaf biomass, stem biomass, inflorescence biomass, and ramet biomass of reproductive ramets in L. chinensis , L. secalinus , C. ripidula , C. pseudophragmites and C. epigeios ( Figure 2 ), and these results supported our first hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have repeatedly revealed that physiological integration between vegetative ramets and vegetative ramets with the same function via a rhizome or stolon has a positive effect on the survival and growth of the ramets ( Evans and Cain, 1995 ; Dong and Alaten, 1999 ; Song et al., 2013 ; Chen et al., 2015 ), but little research has been performed on the effect of physiological integration between vegetative ramets and reproductive ramets with different functions by tillering node connection on sexual reproductive performance. Our previous studies showed that physiological integration between vegetative and reproductive ramets connected by a tillering node increased sexual reproductive characteristics such as inflorescence biomass, floret number, seed number, seed biomass and the seed-setting rate in H. glabra ( Guo et al., 2020b ) and L. chinensis ( Guo et al., 2020c ). In the present study, by severing connections, we found that physiological integration between vegetative ramets and reproductive ramets connected by a tillering node significantly increased the leaf biomass, stem biomass, inflorescence biomass, and ramet biomass of reproductive ramets in L. chinensis , L. secalinus , C. ripidula , C. pseudophragmites and C. epigeios ( Figure 2 ), and these results supported our first hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological integration enables plastic responses to heterogeneous environments and is an advantage for the reproduction of clonal plant (Guo et al, 2020;Wang et al, 2020;Xu et al, 2012). Ramets located in favorable conditions can serve as a donor, supporting recipient ramets suffering from stress (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological integration refers to the transferring and sharing of substances, energy, and signals among sister ramets through their connection by stolon or rhizome (Alpert, 1999). Physiological integration enables plastic responses to heterogeneous environments and is an advantage for the reproduction of clonal plant (Guo et al, 2020; Wang et al, 2020; Xu et al, 2012). Ramets located in favorable conditions can serve as a donor, supporting recipient ramets suffering from stress (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Clonal plants produce their offspring via not only sexual reproduction but also asexual reproduction, in which new individual clones with an identical gene set, called ramets, are generated [ 1 , 2 , 3 , 4 , 5 , 6 ]. Elucidating the mechanism by which clones forage resources in heterogeneous environments is a central issue in clonal plant ecology [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], plant growth modeling [ 23 ], and their application in vegetation management [ 17 , 18 , 19 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Additionally, the spatial arrangement of ramets determines the reproductive success of clonal plants; this is because aggregation of ramets that belong to the same genets leads to an increased percentage of geitonogamous self-pollination [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies on resource foraging of clonal plants were performed using plants that were grown in pots or trays [ 7 , 8 , 9 , 18 , 19 , 24 , 40 , 42 , 44 , 45 , 46 , 47 ] and/or inside laboratories or greenhouses [ 7 , 8 , 19 , 24 , 45 ] rather than in their natural habitats. Nevertheless, it has been discussed that plants respond to their environment in different ways depending on whether they are grown in pots or in their natural habitats [ 5 , 48 , 49 ]. Plants in natural habitats experience greater fluctuations in their environment compared with plants that grow in pots or in greenhouses [ 32 , 48 ].…”
Section: Introductionmentioning
confidence: 99%